On a Class of Degenerate Nonlinear Elliptic Equations in Weighted Sobolev Spaces (Journal of Mathematical Study, 2025)
In this paper we are interested in the existence of solutions for Dirichletproblem associated to the degenerate nonlinear elliptic equationsin the setting of the weighted Sobolev spaces $W^{1,p}_ 0(Ω,ω).$